IMPLEMENTATION OF TOURISM PROMOTION POLICY IN SEMARANG CITY - Permana, Zelado Adhi; Kismartini, Kismartini (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
Implementation of Tourism Promotion Policy in Semarang City is a policy applied in Semarang City based on Local Regulation Number 3 Year 2010, Article 33 paragraph 3 About Tourism. This policy aims to improve the image of tourism and increase the number of tourist visits in the city of Semarang. One way that is done is to form a regional promotion agency regulated in the Mayor of Semarang Regulation No. 2 of 2012 on Tourism Promotion Board of Semarang City. This study aims to determine the implementation of tourism promotion policy in the city of Semarang. The results showed that in the implementation of tourism promotion policy in Semarang City through image enhancement activities such as organizing events such as exhibitions. However, there are still some obstacles in the implementation of tourism policy, especially in the case of Human Resources for the promotional participants and the Fund, especially in the limited access to Grant Fund. It can cause the implementation of tourism promotion policy in Semarang city can be hampered. Based on these obstacles, then made efforts in tackling these constraints by the Department of Culture and Tourism Semarang city in an effort to promote tourism. Things to consider in the promotion of tourism in the city of Semarang is funding support and improvement of human resources by training the executors to make the implementers as actors in the tourism promotion activities are competent.